Composite oxide solid electrolyte sheet and preparation method and application thereof
By forming a lithium aluminate layer on the surface of the oxide solid electrolyte sheet, the problem of low stability of the oxide solid electrolyte to lithium is solved, and the compatibility with the electrode sheet and the rate performance and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202411255522.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-07
AI Technical Summary
The existing oxide solid electrolyte has low stability to lithium, which limits its application in high energy density lithium batteries and has high compatibility and contact impedance with the electrode sheet.
By placing the oxide solid electrolyte sheet in a reaction solution containing lithium and aluminum compounds for heating, a composite oxide solid electrolyte sheet with a surface coated with a lithium aluminate layer is formed. The method includes a first calcination, a heating reaction and a second calcination step to ensure formation and stability of the lithium aluminate layer.
Improves the stability of oxide solid electrolyte to lithium, enhances compatibility with electrode sheets, and reduces contact impedance, thereby improving the rate performance and cycling performance of composite oxide solid electrolyte sheets in all-solid or semi-solid batteries. .
Smart Images

Figure BDA0005033929120000121 
Figure BDA0005033929120000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite oxide solid electrolyte sheet and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in 3C consumer products, electric vehicles, power tools, energy storage and other fields due to their high operating voltage window, high energy density, long cycle life and no memory effect. Lithium-ion batteries using liquid electrolytes are prone to safety hazards such as thermal runaway and fire; solid-state lithium batteries using solid electrolytes can fundamentally solve the safety problem of batteries.
[0003] Solid electrolytes are the core of solid-state batteries and directly determine the performance of the battery. They are mainly divided into polymer electrolytes, sulfide electrolytes and oxide electrolytes. Among them, polymer electrolytes have the advantages of easy processing and good elasticity, but they have low ionic conductivity, high operating temperature and narrow chemical window; although sulfide electrolytes have high ionic conductivity, they are sensitive to air, easy to oxidize, and easy to react with water to produce H2S, which has strict requirements on the production environment; oxide electrolytes have high ionic conductivity, high chemical stability and excellent comprehensive performance, and have received widespread attention, but this type of material has the problem of low stability to lithium.
[0004] Oxide solid electrolytes are mainly divided into thin film type, LISICON type, NaSICON type, perovskite type, garnet type, etc. Among them, when lithium aluminum titanium phosphate LATP comes into contact with Li metal, Ti 4+ It is easily reduced to Ti at low potential. 3+ Therefore, it cannot directly contact with metallic Li or low-potential Li-embedded negative electrode materials; the tetravalent Ge in lithium aluminum germanium phosphate LAGP is still reduced after contact with the metallic lithium negative electrode; Li with perovskite structure 3x La (2 / 3)-x M (1 / 3)-2x TiO3 also has similar problems. The low stability of the above-mentioned oxide solid electrolyte to lithium seriously limits the application of oxide solid electrolyte materials in high energy density lithium batteries. Summary of the invention
[0005] A technical problem to be solved by the present invention is how to provide a composite oxide solid electrolyte sheet and its preparation method and application, so that the grain boundary impedance of the composite oxide solid electrolyte sheet is low, the ionic conductivity is high, and the stability of the oxide solid electrolyte to lithium is improved, the compatibility of the oxide solid electrolyte with the electrode sheet is improved, and the contact impedance is reduced; when the composite oxide solid electrolyte sheet of the present invention is applied to an all-solid-state battery or a semi-solid-state battery, it can have good rate performance and cycle performance.
[0006] In order to solve the above technical problems, an embodiment of the present invention provides a method for preparing a composite oxide solid electrolyte sheet, which comprises the following steps:
[0007] 1) pressing the oxide solid electrolyte powder into sheets, and first calcining to obtain an oxide solid electrolyte sheet;
[0008] 2) placing the oxide solid electrolyte sheet in a reaction solution and heating it for reaction; the reaction solution comprises a lithium-containing compound and an aluminum-containing compound;
[0009] 3) The oxide solid electrolyte sheet after the reaction is subjected to a second calcination to obtain a composite oxide solid electrolyte sheet with a lithium aluminate layer coated on the surface.
[0010] In some embodiments, the solvent of the reaction solution is selected from at least one of water, ethanol, isopropanol and n-butanol; the molar concentration of lithium element in the reaction solution is 0.1-1 mol / L; the molar ratio of lithium element to aluminum element in the reaction solution is 1:0.8-1.2.
[0011] In some embodiments, the lithium-containing compound is selected from any one of lithium nitrate, lithium hydroxide, lithium carbonate, lithium ethoxide and lithium isopropoxide; the aluminum-containing compound is selected from any one of aluminum nitrate, aluminum hydroxide, aluminum sulfate, aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide.
[0012] In some embodiments, the first calcination includes a heating process and a heat preservation process, wherein the heating rate is 1-5°C / min, the heat preservation temperature is 500-1400°C, and the heat preservation time is 1-16h.
[0013] In some embodiments, the reaction temperature of the heating reaction is 60 to 200° C., and the reaction time is 1 to 48 hours.
[0014] In some embodiments, the calcination temperature of the second calcination is 400-1000° C., and the calcination time is 1-24 hours.
[0015] In some embodiments, the thickness of the lithium aluminate layer is 1 to 20 nm.
[0016] In order to solve the above technical problems, an embodiment of the present invention further provides a composite oxide solid electrolyte sheet, which includes:
[0017] The core layer is an oxide solid electrolyte sheet;
[0018] The coating layer is coated on the surface of the core layer; the coating layer is a lithium aluminate layer with a thickness of 1 to 20 nm.
[0019] In some embodiments, it is prepared according to the aforementioned method for preparing a composite oxide solid electrolyte sheet.
[0020] In order to solve the above technical problems, an embodiment of the present invention further provides an application of the aforementioned composite oxide solid electrolyte sheet in an all-solid-state battery or a semi-solid-state battery.
[0021] Through the above technical scheme, the present invention provides a composite oxide solid electrolyte sheet and a preparation method and application thereof, which first presses the oxide solid electrolyte powder into sheets, and sinters the oxide solid electrolyte powder through a first calcination to gradually turn it into a dense oxide solid electrolyte sheet; then puts the dense oxide solid electrolyte sheet into a reaction solution including a lithium-containing compound and an aluminum-containing compound, reacts at a certain temperature for a period of time, so that the surface of the oxide solid electrolyte sheet is coated with a lithium aluminate layer, and takes it out and performs a second calcination, so that a lithium aluminate layer is formed on the surface of the oxide solid electrolyte, and a composite solid electrolyte sheet with a lithium aluminate layer coated on the surface is obtained; lithium aluminate is an ion conductor, which can be used as a coating material to be coated on the surface of the positive electrode material, and the presence of the lithium aluminate coating layer can increase the compatibility between the oxide solid electrolyte sheet and the electrode material, reduce the contact impedance between the solid electrolyte and the electrode sheet, and thus improve the rate performance. When the composite oxide solid electrolyte sheet prepared by the technical solution of the present invention is matched with lithium metal to form a solid-state battery, the lithium aluminate coating layer can avoid contact between the oxide solid electrolyte and the lithium metal, thereby improving the stability of the oxide solid electrolyte to lithium, improving the compatibility of the oxide solid electrolyte with the pole piece, and reducing the contact impedance. When the composite oxide solid electrolyte sheet of the present invention is applied to an all-solid-state battery or a semi-solid-state battery, it can have good rate performance and cycle performance.
[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0023] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the following is a detailed description of a composite oxide solid electrolyte sheet and its preparation method and application proposed in accordance with the present invention, its specific implementation method, structure, characteristics and effects, in combination with the preferred embodiments.
[0024] The present invention proposes a composite oxide solid electrolyte sheet, which structurally includes a core layer and a coating layer; wherein the material of the core layer is an oxide solid electrolyte, and the coating layer is a lithium aluminate layer coated on the surface of the core layer. The lithium aluminate coating layer can avoid contact between the oxide solid electrolyte and lithium metal, thereby improving the stability of the oxide solid electrolyte to lithium, improving the compatibility of the oxide solid electrolyte with the pole piece, and reducing the contact impedance.
[0025] The preferred coating thickness is 1 to 20 nm. If the coating is too thin, the contact between the oxide solid electrolyte and the lithium metal cannot be avoided, and the aforementioned effect cannot be achieved; if the coating is too thick, the Li + The obstacles to diffusion and migration, which in turn affect charge transfer and ion migration, will reduce the ionic conductivity, specific capacity and rate performance of the prepared composite oxide solid electrolyte sheet.
[0026] The oxide electrolyte used in the present invention is selected from at least one of a NASICON structure, a LISICON structure, a perovskite structure and a garnet structure; NASICON structure and a perovskite structure are further preferred; it can be purchased commercially or prepared by itself, which is not a key point of the present invention and is not specifically limited in the present invention.
[0027] The present invention also provides a method for preparing a composite oxide solid electrolyte sheet, which comprises the following steps:
[0028] 1) pressing the oxide solid electrolyte powder into sheets and performing a first calcination to obtain a dense oxide solid electrolyte sheet;
[0029] 2) placing the dense oxide solid electrolyte sheet in a reaction solution comprising a lithium-containing compound and an aluminum-containing compound, and heating the solution to cause a reaction;
[0030] 3) Finally, the oxide solid electrolyte sheet after the reaction is subjected to a second calcination to form a lithium aluminate layer on the surface of the dense oxide solid electrolyte sheet, thereby obtaining a composite oxide solid electrolyte sheet with a lithium aluminate layer coated on the surface.
[0031] The technical purpose of the first calcination is to sinter the oxide electrolyte sheet into a dense electrolyte sheet, which can be sintered using a conventional sintering process in the prior art. The first calcination preferably includes a heating process and a heat preservation process, wherein the heating rate is 1 to 5°C / min, the heat preservation temperature is 500 to 1400°C, and the heat preservation time is 1 to 16h.
[0032] The key step in the technical solution of the present invention is to place a dense oxide solid electrolyte sheet in a reaction solution for chemical reaction, and then perform a second calcination on the reacted oxide solid electrolyte sheet so that its surface is coated with a lithium aluminate layer.
[0033] The lithium-containing compound contained in the reaction solution may be any one of lithium nitrate, lithium hydroxide, lithium carbonate, lithium ethoxide and lithium isopropoxide; the aluminum-containing compound may be any one of aluminum nitrate, aluminum hydroxide, aluminum sulfate, aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide. The aforementioned lithium-containing compound and aluminum-containing compound may be combined in any way.
[0034] The reaction solution preferably has a solvent of at least one of water, ethanol, isopropanol and n-butanol; wherein, in the reaction solution, the molar ratio of lithium element to aluminum element is 1:0.6-1.4; preferably, the molar ratio of lithium element to aluminum element in the reaction solution is 1:0.8-1.2; further preferably, the molar ratio of lithium element to aluminum element in the reaction solution is 1:1; and the molar concentration of lithium element is 0.1-1 mol / L.
[0035] The reaction temperature and reaction time of the heating reaction will affect the thickness of the final lithium aluminate layer. In some embodiments, the reaction temperature of the heating reaction is 60 to 200°C, and the reaction time is 1 to 48 hours. Under this condition, the lithium-containing compound and the aluminum-containing compound in the reaction solution can generate lithium aluminate, and the generated lithium aluminate is adsorbed by the dense oxide solid electrolyte sheet and gradually forms a deposit.
[0036] The present invention performs a second calcination on the oxide solid electrolyte sheet after the heating reaction. In some embodiments, the calcination temperature is 400-1000°C, and the preferred calcination temperature is 700-1000°C; the calcination time is 1-24h. The purpose of the second calcination in the present invention is: on the one hand, other amorphous components (such as aluminum hydroxide gel) generated in the aforementioned heating reaction except lithium aluminate are decomposed under high temperature conditions to form lithium aluminate, so that all the substances coated on the oxide solid electrolyte sheet are lithium aluminate; on the other hand, the secondary calcination at an increased temperature can make the crystal form of the generated lithium aluminate mainly γ-LiAlO2, and γ-LiAlO2 is structurally stable in a high temperature environment without phase change, thereby improving the chemical stability of the oxide solid electrolyte sheet prepared by the present invention.
[0037] Based on the above, the second calcination in the present invention is beneficial to improving the ionic conductivity of the prepared composite oxide solid electrolyte sheet and improving the rate performance and cycle performance of the composite oxide solid electrolyte sheet.
[0038] The present invention also proposes an application of the composite oxide solid electrolyte sheet in an all-solid battery or a semi-solid battery. When the composite oxide solid electrolyte sheet of the present invention is applied to an all-solid battery or a semi-solid battery, it can have better rate performance and cycle performance.
[0039] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0040] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0041] Embodiment 1:
[0042] This embodiment prepares a kind of lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) composite oxide solid electrolyte sheet, the specific steps are as follows:
[0043] 1) Preparation of oxide solid electrolyte sheet:
[0044] Commercially available lithium aluminum titanate phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) oxide electrolyte powder was pressed into a sheet with a diameter of 16 mm and a thickness of 1 mm at a pressure of 200 MPa; the sheet was placed in a high-temperature furnace for calcination. The process parameters are shown in Table 1, that is, the temperature was increased to 950°C at a heating rate of 5°C / min, calcined for 6 hours under this temperature condition, cooled to room temperature, taken out, and polished to obtain an oxide solid electrolyte sheet.
[0045] 2) Prepare the reaction solution:
[0046] Weigh lithium nitrate and aluminum nitrate. The relevant parameters in the preparation process can be seen in Table 1, that is, the molar ratio of lithium to aluminum elements is controlled to be 1:1; dissolve the weighed lithium nitrate and aluminum nitrate in deionized water, and adjust the amount of water so that the molar concentration of lithium nitrate is 0.2 mol / L.
[0047] 3) Lithium aluminate is coated on the surface of the oxide solid electrolyte sheet:
[0048] The oxide solid electrolyte sheet prepared in this embodiment is placed in the prepared reaction solution, and then the whole (i.e., the whole including the oxide solid electrolyte sheet and the prepared reaction solution) is placed in a reactor for heating reaction. The reaction conditions can be seen in Table 1, that is, heating to 120° C., keeping the temperature under this temperature condition for 4 hours, and adsorbing and depositing lithium aluminate on the surface of the oxide solid electrolyte sheet through the heating reaction to form a lithium aluminate layer.
[0049] 4) Second calcination to prepare composite oxide solid electrolyte sheet
[0050] The oxide solid electrolyte sheet formed by heating the reaction liquid to form a lithium aluminate layer is taken out from the reaction liquid, and then placed in a high-temperature furnace for a second calcination. The process conditions of the second calcination can be seen in Table 1, that is, calcining at 800°C for 2h, cooling to room temperature, and obtaining a composite oxide solid electrolyte sheet. The thickness of the lithium aluminate layer coated on the prepared composite oxide solid electrolyte sheet is measured, and the results are shown in Table 1, that is, the lithium aluminum titanium phosphate Li prepared in this embodiment 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is 3nm.
[0051] 5) Performance testing
[0052] The composite oxide solid electrolyte sheet prepared in this embodiment was subjected to ion conductivity test, rate performance test and cycle performance test. The specific method is as follows:
[0053] A. Ionic conductivity test:
[0054] The ionic conductivity of the solid electrolyte is obtained by assembling a blocking electrode and performing an electrochemical impedance spectroscopy (EIS) test. The specific operation method is as follows:
[0055] The composite oxide solid electrolyte sheet prepared in this embodiment has stainless steel sheets as blocking electrodes on both sides to form a symmetrical battery; the electrochemical workstation used is DH7001, and the frequency range is 0.01~10 6 Hz, test the EIS of oxide solid electrolyte sheets at 25°C. The ionic conductivity of the solid electrolyte is calculated as follows:
[0056] δ=L / (R·S)
[0057] Where, δ is the ionic conductivity (unit S / cm), L is the thickness of the solid electrolyte sheet (unit cm), R is the intrinsic resistance of the solid electrolyte (unit Ω), S is the effective cross-sectional area of the solid electrolyte sheet (unit cm 2 ). The higher the test result of ionic conductivity, the better the ionic conductivity. The test results are shown in Table 2.
[0058] B. Rate performance test:
[0059] Make a solid-state battery with lithium cobalt oxide as the positive electrode and metallic lithium as the negative electrode to evaluate the rate performance of the oxide solid electrolyte. The specific operation method is as follows:
[0060] Lithium cobalt oxide, conductive agent Super P, and binder PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 9:0.5:0.5, and an appropriate amount of solvent NMP (N-methylpyrrolidone) was added and stirred to prepare a positive electrode slurry, which was coated on aluminum foil, dried at 100°C, and then cut into discs with a diameter of 10 mm as positive electrodes. CR2032 button batteries were assembled in the order of positive electrode sheet-composite oxide solid electrolyte sheet-lithium foil. Battery rate test was performed.
[0061] The operating voltage range of the all-solid-state lithium secondary battery is set to 3V to 4.2V, and the current density is 0.15 mA / cm 2 ) to 4.2V, and then constant voltage to 0.01C cut-off; then discharge to 3V at 0.1C, 0.2C, 0.5C, 1C currents, respectively, to obtain the gram capacity of the material at 0.1C, 0.2C, 0.5C, 1C discharge rates. The test results are shown in Table 3.
[0062] C. Cycle performance test:
[0063] Assemble CR2032 button cells according to the rate performance test method. 2 ) to 4.2V, then constant voltage to 0.05C cut-off, and 100 cycles were performed respectively to calculate the capacity retention rate. The results are shown in Table 4.
[0064] Example 2
[0065] This example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet is different from Example 1 only in the process parameters of each step. The specific parameters can be seen in Table 1.
[0066] The lithium aluminum titanium phosphate prepared in this example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0067] The lithium aluminum titanium phosphate Li prepared in this example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0068] Example 3
[0069] This example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet is different from Example 1 only in the process parameters of each step. The specific parameters can be seen in Table 1.
[0070] The lithium aluminum titanium phosphate prepared in this example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0071] The lithium aluminum titanium phosphate Li prepared in this example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0072] Example 4
[0073] This example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet is different from Example 1 only in the process parameters of each step. The specific parameters can be seen in Table 1.
[0074] The lithium aluminum titanium phosphate prepared in this example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0075] The lithium aluminum titanium phosphate Li prepared in this example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0076] Example 5
[0077] This example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7The (PO4)3(LATP) composite oxide solid electrolyte sheet is different from Example 1 only in the process parameters of each step. The specific parameters can be seen in Table 1.
[0078] The lithium aluminum titanium phosphate prepared in this example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0079] The lithium aluminum titanium phosphate Li prepared in this example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0080] Example 6
[0081] This embodiment prepares a kind of lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) composite oxide solid electrolyte sheet, which is different from Example 1 in that:
[0082] In the process of preparing the reaction solution in this embodiment, lithium carbonate and aluminum sulfate are weighed to control the molar ratio of lithium to aluminum to be 1:1; the weighed lithium carbonate and aluminum hydroxide are dissolved in deionized water, and the amount of water is adjusted so that the molar concentration of lithium carbonate is 0.2 mol / L.
[0083] The other preparation steps and process parameters are the same as those in Example 1.
[0084] The lithium aluminum titanium phosphate prepared in this example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0085] The lithium aluminum titanium phosphate Li prepared in this example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0086] Comparative Example 1
[0087] This comparative example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti1.7 (PO4)3(LATP) oxide solid electrolyte sheet, the specific steps are as follows:
[0088] 1) Preparation of oxide solid electrolyte sheet:
[0089] Commercially available lithium aluminum titanate phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) oxide electrolyte powder was pressed into a sheet with a diameter of 16 mm and a thickness of 1 mm at a pressure of 200 MPa; the sheet was placed in a high-temperature furnace for calcination. The process parameters are shown in Table 1, that is, the temperature was increased to 950°C at a heating rate of 5°C / min, and then calcined for 6 hours under this temperature condition, cooled to room temperature, taken out, and polished to obtain an oxide solid electrolyte sheet.
[0090] 2) Heating reaction blank control:
[0091] The oxide solid electrolyte sheet prepared in this comparative example was placed in a deionized water solution, and the whole was placed in a reactor for heating reaction. The reaction conditions can be seen in Table 1, that is, heated to 120° C. and then kept at this temperature for 4 hours.
[0092] 3) Second calcined oxide solid electrolyte sheet
[0093] The oxide solid electrolyte sheet was taken out after being heated to 120°C in the aqueous solution and reacted for 4 hours, and then placed in a high-temperature furnace for a second calcination. The process conditions of the second calcination can be seen in Table 1, that is, calcined at 800°C for 2 hours, cooled to room temperature, and obtained the oxide solid electrolyte sheet of this comparative example.
[0094] The lithium aluminum titanium phosphate Li prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) oxide solid electrolyte sheet was tested for ionic conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0095] Comparative Example 2
[0096] This comparative example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet has a preparation method substantially the same as that of Example 1, except that:
[0097] In the process of preparing the reaction solution of this comparative example, lithium nitrate and aluminum nitrate were weighed. The relevant parameters in the preparation process can be seen in Table 1, that is, the amount of water in the reaction solution was adjusted to make the molar concentration of lithium nitrate 0.05 mol / L.
[0098] The other preparation steps and process parameters are the same as those in Example 1. The specific relevant process parameters can be seen in Table 1.
[0099] The lithium aluminum titanium phosphate prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0100] The lithium aluminum titanium phosphate Li prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0101] Comparative Example 3
[0102] This comparative example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet has a preparation method substantially the same as that of Example 1, except that:
[0103] In the process of preparing the reaction solution of this comparative example, lithium nitrate and aluminum nitrate were weighed. The relevant parameters in the preparation process can be seen in Table 1, that is, the amount of water in the reaction solution was adjusted to make the molar concentration of lithium nitrate 1.5 mol / L.
[0104] The other preparation steps and process parameters are the same as those in Example 1. The specific relevant process parameters can be seen in Table 1.
[0105] The lithium aluminum titanium phosphate prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0106] The lithium aluminum titanium phosphate Li prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0107] Comparative Example 4
[0108] This comparative example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet has a preparation method substantially the same as that of Example 1, except that:
[0109] In the process of preparing the reaction solution in this comparative example, lithium nitrate and aluminum nitrate were weighed, and the relevant parameters in the preparation process can be seen in Table 1, that is, the amount of water in the reaction solution was adjusted so that the molar concentration of lithium nitrate was 1 mol / L. In addition, in the process of depositing and coating lithium aluminate on the surface of the oxide solid electrolyte sheet in this comparative example, it was heated to 220°C, and then kept at this temperature for 50 hours.
[0110] The other preparation steps and process parameters are the same as those in Example 1. The specific relevant process parameters can be seen in Table 1.
[0111] The lithium aluminum titanium phosphate prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0112] The lithium aluminum titanium phosphate Li prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0113] Comparative Example 5
[0114] This comparative example prepares a lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet has a preparation method substantially the same as that of Example 1, except that:
[0115] In the second calcination process for preparing the composite oxide solid electrolyte sheet in this comparative example, the composite oxide solid electrolyte sheet was calcined at 300° C. for 2 h and then cooled to room temperature to obtain the composite oxide solid electrolyte sheet.
[0116] The other preparation steps and process parameters are the same as those in Example 1. The specific relevant process parameters can be seen in Table 1.
[0117] The lithium aluminum titanium phosphate prepared in this comparative example 1.3 Al 0.3Ti 1.7 The thickness of the lithium aluminate layer coated on the (PO4)3(LATP) composite oxide solid electrolyte sheet is shown in Table 1.
[0118] The lithium aluminum titanium phosphate Li prepared in this comparative example 1.3 Al 0.3 Ti 1.7 The (PO4)3(LATP) composite oxide solid electrolyte sheet was tested for ion conductivity, rate performance and cycle rate performance, and the testing method was the same as in Example 1.
[0119] The process parameters involved in the preparation of oxide solid electrolyte sheets in the embodiments of the present invention and the comparative examples are shown in Table 1:
[0120] Table 1 Relevant process parameters involved in the examples and comparative examples
[0121]
[0122] Table 2 Ionic conductivity test results of various embodiments and comparative examples
[0123] Group Ionic conductivity (S / cm) Example 1 <![CDATA[9.12×10 -4 ]]> Example 2 <![CDATA[9.45×10 -4 ]]> Example 3 <![CDATA[9.81×10 -4 ]]> Example 4 <![CDATA[9.01×10 -4 ]]> Example 5 <![CDATA[9.03×10 -4 ]]> Example 6 <![CDATA[9.13×10 -4 ]]> Comparative Example 1 <![CDATA[2.93×10 -4 ]]> Comparative Example 2 <![CDATA[3.02×10 -4 ]]> Comparative Example 3 <![CDATA[4.76×10 -4 ]]> Comparative Example 4 <![CDATA[4.68×10 -4 ]]> Comparative Example 5 <![CDATA[4.73×10 -4 ]]>
[0124] Table 3 Rate performance test results of various embodiments and comparative examples
[0125]
[0126] Table 4 Cyclic performance test results of various embodiments and comparative examples
[0127] Group 50 cycle capacity retention rate (%) 100 cycle capacity retention rate (%) Example 1 96.2 93.5 Example 2 97.2 94.6 Example 3 97.5 95.3 Example 4 96.9 94.0 Example 5 95.9 93.1 Example 6 96.0 93.3 Comparative Example 1 90.3 81.5 Comparative Example 2 91.8 85.2 Comparative Example 3 91.3 84.2 Comparative Example 4 90.7 83.1 Comparative Example 5 90.5 83.5
[0128] Combining Examples 1-6 and Tables 1, 2, 3, 4 and Comparative Example 1, it can be seen that the lithium aluminum titanium phosphate Li prepared by the preparation method of the present invention 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) composite oxide solid electrolyte sheet, in the oxide lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 Coating the surface of the (PO4)3(LATP) solid electrolyte sheet with a lithium aluminate layer can significantly increase the ionic conductivity of the solid electrolyte sheet and improve the rate performance and cycle performance of the solid electrolyte sheet.
[0129] Combining Examples 1-6, Comparative Examples 1-3, and Tables 1-4, it can be seen that the method of the present invention is used to prepare aluminum titanate phosphate Li 1.3 Al 0.3 Ti 1.7In the process of preparing (PO4)3(LATP) composite oxide solid electrolyte sheet, in the prepared reaction solution, the amount of water is adjusted so that the molar concentration of lithium nitrate is 0.1-1 mol / L, and the molar ratio of the lithium-containing compound to the aluminum-containing compound in the reaction solution is 1:0.8-1.2, which is beneficial to improve the ionic conductivity of the composite oxide solid electrolyte sheet, and improve the cycle performance and rate performance of the composite oxide solid electrolyte sheet. Analysis of the reasons shows that: since the aluminum element in the reaction solution can react with water to generate hydrogen ions, making the solution weakly acidic, the reaction solution corrodes the surface of the oxide solid electrolyte sheet in the reaction solution, so that more active interfaces are exposed on the surface of the oxide solid electrolyte sheet, which is beneficial to the adsorption of lithium aluminate, and then it is beneficial to wrap the aluminate layer on the surface of the oxide solid electrolyte sheet, improve the ionic conductivity of the oxide solid electrolyte sheet, and improve the cycle performance and rate performance of the ionic conductivity of the oxide solid electrolyte sheet; however, when the molar concentrations of the aluminum and lithium elements in the reaction solution are too high, that is, the molar concentration of the lithium element is greater than When the concentration of lithium aluminate in the composite oxide solid electrolyte sheet is 1 mol / L, the thickness of the lithium aluminate layer coated on the composite oxide solid electrolyte sheet is too thick, which inhibits the migration of lithium ions and is not conducive to the improvement of the relevant performance of the composite oxide solid electrolyte sheet; and under the reaction conditions, the surface of the oxide solid electrolyte sheet is severely corroded, so that more lithium ions and aluminum ions in the reaction solution enter the structure of the oxide solid electrolyte sheet, which may cause the lithium ion channels inside the oxide solid electrolyte sheet to be blocked, which is not conducive to improving the ionic conductivity of the oxide solid electrolyte sheet, nor is it conducive to improving the cycle performance and rate performance of the ionic conductivity of the oxide solid electrolyte sheet. When the molar concentrations of aluminum and lithium in the reaction solution are too low, that is, when the molar concentration of lithium is less than 0.1 mol / L, it is not conducive to exposing more active interfaces on the surface of the oxide solid electrolyte sheet, and is thus not conducive to the adsorption of lithium aluminate by the oxide solid electrolyte sheet; in addition, the lithium and aluminum content in the reaction solution is low, and the content of lithium aluminate generated during the heating reaction is small, so the content of the target product deposited on the surface of the oxide solid electrolyte sheet is small, and as a result, after the oxide solid electrolyte sheet deposited on the surface by the heating reaction passes through the second calcination, the thickness of the lithium aluminate layer coated on the obtained composite oxide solid electrolyte sheet is too thin, and the purity of the lithium aluminate in the coated lithium aluminate layer is reduced, which is not conducive to improving the ionic conductivity of the composite oxide solid electrolyte sheet, nor is it conducive to improving the cycle performance and rate performance of the composite oxide solid electrolyte sheet.
[0130] Combining Example 1, Comparative Example 1, and Comparative Example 4, it can be seen from Tables 1-4 that Comparative Example 4 is effective in preparing lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7(PO4)3(LATP) composite oxide solid electrolyte sheet process, the oxide solid electrolyte sheet is placed in a reaction solution for heating reaction, the heating temperature is 220 ° C, the insulation reaction time is 50h, the final composite oxide solid electrolyte sheet coated with lithium aluminate layer thickness is 28nm, compared with the composite oxide solid electrolyte sheet prepared in comparative example 1, the composite oxide solid electrolyte sheet prepared in comparative example 4 has improved ion conductivity, but compared with example 1, the ion conductivity is significantly reduced, the rate performance and cycle performance are significantly reduced, the reason may be that: in the preparation method of comparative example 4, when the oxide solid electrolyte sheet is placed in a reaction solution for heating reaction, the heating reaction temperature is high, which aggravates the reaction process, and the reaction time is too long, so that the thickness of the coating layer of the composite oxide solid electrolyte sheet finally formed is too thick, increasing Li + The obstacles to diffusion and migration, in turn, affect charge transfer and ion migration, which in turn reduces the ionic conductivity, cycle performance and rate performance of the prepared composite oxide solid electrolyte sheet.
[0131] Combining Example 1, Comparative Example 1, Comparative Example 5, and Tables 1-4, it can be seen that in Comparative Example 5, in the preparation of lithium aluminum titanium phosphate Li 1.3 Al 0.3 Ti 1.7 (PO4)3(LATP) composite oxide solid electrolyte sheet process, in the second calcination process, the calcination temperature is 300 ° C. Compared with the ionic conductivity of the oxide solid electrolyte sheet prepared in Comparative Example 1, the ionic conductivity of the composite oxide solid electrolyte sheet prepared in Comparative Example 5 is improved, but compared with Example 1, the ionic conductivity is significantly reduced, and the rate performance and cycle performance are significantly reduced. The reason may be that: since the temperature of the second calcination is too low, part of the amorphous material (such as aluminum hydroxide gel) in the deposit formed on the surface of the oxide solid electrolyte sheet after the heating reaction in Comparative Example 5 is not decomposed during the second calcination process, which reduces the purity of lithium aluminate in the lithium aluminate layer coated on the surface of the composite oxide solid electrolyte sheet, which is not conducive to improving the ionic conductivity of the composite oxide solid electrolyte sheet, nor is it conducive to improving the cycle performance and rate performance of the composite oxide solid electrolyte sheet. In addition, since the temperature of the second calcination in the preparation method of Comparative Example 5 is too low, the crystal form of lithium aluminate in the lithium aluminate layer coated with the composite oxide solid electrolyte sheet prepared thereby may also contain relatively more β-LiAlO2, and the structural stability of β-LiAlO2 is poor. Therefore, the cycle performance and rate performance of the composite oxide solid electrolyte sheet prepared thereby are significantly reduced compared with those in Example 1.
[0132] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.
[0133] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite oxide solid electrolyte sheet, characterized in that: It includes the following steps: 1) pressing the oxide solid electrolyte powder into sheets, and first calcining to obtain an oxide solid electrolyte sheet; 2) placing the oxide solid electrolyte sheet in a reaction solution and heating it for reaction; the reaction solution comprises a lithium-containing compound and an aluminum-containing compound; 3) The oxide solid electrolyte sheet after the reaction is subjected to a second calcination to obtain a composite oxide solid electrolyte sheet with a lithium aluminate layer coated on the surface.
2. The preparation method according to claim 1, characterized in that: The solvent of the reaction solution is selected from at least one of water, ethanol, isopropanol and n-butanol; the molar concentration of lithium in the reaction solution is 0.1-1 mol / L; and the molar ratio of lithium to aluminum in the reaction solution is 1:0.8-1.
2.
3. The preparation method according to claim 1, characterized in that: The lithium-containing compound is selected from any one of lithium nitrate, lithium hydroxide, lithium carbonate, lithium ethoxide and lithium isopropoxide; the aluminum-containing compound is selected from any one of aluminum nitrate, aluminum hydroxide, aluminum sulfate, aluminum ethoxide, aluminum isopropoxide and aluminum sec-butoxide.
4. The preparation method according to claim 1, characterized in that: The first calcination includes a heating process and a heat preservation process, wherein the heating rate is 1-5°C / min, the heat preservation temperature is 500-1400°C, and the heat preservation time is 1-16h.
5. The preparation method according to claim 1, characterized in that: The reaction temperature of the heating reaction is 60-200° C., and the reaction time is 1-48 hours.
6. The preparation method according to claim 1, characterized in that: The calcination temperature of the second calcination is 400-1000° C., and the calcination time is 1-24 hours.
7. The preparation method according to claim 1, characterized in that: The thickness of the lithium aluminate layer is 1 to 20 nm.
8. A composite oxide solid electrolyte sheet, characterized in that: It includes: The core layer is an oxide solid electrolyte sheet; A coating layer, coating the surface of the core layer; The coating layer is a lithium aluminate layer with a thickness of 1 to 20 nm.
9. The composite oxide solid electrolyte sheet according to claim 8, characterized in that: The composite oxide solid electrolyte sheet is prepared according to the method for preparing the composite oxide solid electrolyte sheet according to any one of claims 1 to 7.
10. Use of the composite oxide solid electrolyte sheet according to claim 8 or 9 in an all-solid-state battery or a semi-solid-state battery.
Citation Information
Cited By
Inorganic solid electrolyte preparation method for pre-constructing ion rapid transmission interface through in-situ heat treatment
CN122370481A